Maternal death in the visual arts: immersion into emotional world through the great artists' paintings - N. A. Makatsariya; V. O. Bitsadze; J. Kh. Khizroeva; F. A. Chervenak; A. D. Makatsariya (Акушерство, гинекология и репродукция)
The article presents paintings by famous artists on "maternal death": Edvard Munch "The Dead Mother and Child", Pablo Picasso "Motherhood", Egon Schiele "Pregnant Woman and Death" and "The Dying Mother", Frida Kahlo "My Birth", Gustav Klimt "Death and Life" as well as their description.